Comparative Analysis of an Apartment Building using Seismic Codes NBC 105:1994 and NBC 105:2020 (A Case Study) - Malla, Suraj; Alagirisamy, Mukil; Dangol, Purushotam; Giri, Om Prakash (Engineering, Technology & Applied Science Research, 2024)
The present study undertakes a comparative analytical examination of seismic analysis standards in Nepal, focusing on NBC 105:1994 and the updated NBC 105:2020, encompassing both the Ultimate Limit State (ULS) and Serviceability Limit State (SLS). Employing a regular Reinforced Concrete (RC) apartment building in Pokhara as a case study, the geometric and sectional configurations of structural elements are intentionally kept consistent for comparison. The analysis involves creating a 3D model using ETABS version 19, encompassing linear static, Equivalent Static (ES), and linear dynamic Response Spectrum (RS) analyses, followed by nonlinear static (pushover) analysis. The results highlight substantial differences between the two codes. Base shear from NBC 105:2020 is notably higher, being 28.59% ULS and 22.74% SLS greater than NBC 105:1994. The scale factor for combined response design values is significantly lower in both X and Y directions for NBC 105:2020. Story shear is extended by 33% ES and 37% RS with NBC 105:2020 compared to NBC 105:1994. Maximum design displacement and Inter-Story Drift (ISD) are markedly higher with NBC 105:2020, indicating its more severe seismic parameters. This study emphasized the enhanced seismic resilience provided by NBC 105:2020, particularly evident in increased base shear, reduced design scale factors, and higher values for story shear, displacement, and ISD. These findings contribute valuable insights into the seismic design improvements introduced in Nepal's seismic codes after the Gorkha Earthquake in 2015.